Influence of Continuous Training on Atrial Myocytes IK1 and IKAch and on Induction of Atrial Fibrillation in a Rabbit Model - Dou Yuan; Ping Zheng; Chen Tan; Si Hui Huang; Dan Li; Jian Huang (Cardiology Research and Practice)
Background. Elucidation of mechanisms underlying continuous training-related atrial fibrillation (AF) may inform formulation of novel therapeutic approaches and training method selection. This study was aimed at assessing mechanisms underlying continuous training-induced AF in an animal model. Methods. Healthy New Zealand rabbits were divided into three groups (n=8 each), namely, control (C), and moderate intensity (M), and high intensity (H) continuous training according to treadmill speed. Atrial size andintrinsic and resting heart rates were measured by transthoracic echocardiography before, and 8 and 12 weeks after training. Using a Langendorff perfusion system, AF was induced by S1S2 stimulation and the induction rate was recorded. Atrial IK1 and IKAch ion current densities were recorded using whole-cell patch-clamp technique in isolated atrial myocytes. Changes in atrial Kir2.1, Kir2.2, Kir3.1, and Kir3.4 mRNA expression were assessed by reverse transcriptase-coupled polymerase chain reaction. Results. After 8 and 12 weeks, Groups M and H vs. Group C had greater (all P<0.05) atrial anteroposterior diameter; greater incidence of AF (60% and 90% vs. 45%, respectively; P<0.05, also between Groups H and M); and greater atrial IKAch current density. In Group H, Kir2.1 and Kir2.2 mRNA expression in the left and right atria was increased (P<0.05, vs. Groups C and M) as was left atrial Kir3.1 and Kir3.4 mRNA expression (P<0.05, vs. Group C). Conclusion. In a rabbit model, continuous training enlarges atrial diameter leading to atrial structural and electrical remodeling and increased AF incidence.